2011
DOI: 10.1016/j.cplett.2011.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric spectroscopy of water at low frequencies: The existence of an isopermitive point

Abstract: We have studied the real part of the dielectric constant of water from 100 Hz to 1 MHz. We have found that there is a frequency where the dielectric constant is independent of temperature, and called this the isopermitive point. Below this point the dielectric constant increases with temperature, above, it decreases. To understand this behavior, we consider water as a system of two species: ions and dipoles. The first give rise to the so called Maxwell-Wagner-Sillars effect, the second obey the Maxwell-Boltzma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 22 publications
3
25
0
Order By: Relevance
“…Polarization currents have a large and striking dependence on time in almost all materials, even in the solid phase, and is a main subject of classical work (Debye and Falkenhagen 1928, Fuoss 1949, Fröhlich 1958, Van Beek 1967, Nee and Zwanzig 1970, Böttcher, van Belle et al 1978, Barthel, Buchner et al 1995, Kurnikova, Waldeck et al 1996, Buchner and Barthel 2001, Heinz, van Gunsteren et al 2001, Kremer and Schönhals 2003, Rotenberg, Dufre Che et al 2005, Kuehn, Marohn et al 2006, Angulo-Sherman and Mercado-Uribe 2011. The practical importance of the time dependence is well known to the engineers who design solid state devices that work.…”
Section: Polarization Charge and Currentmentioning
confidence: 99%
“…Polarization currents have a large and striking dependence on time in almost all materials, even in the solid phase, and is a main subject of classical work (Debye and Falkenhagen 1928, Fuoss 1949, Fröhlich 1958, Van Beek 1967, Nee and Zwanzig 1970, Böttcher, van Belle et al 1978, Barthel, Buchner et al 1995, Kurnikova, Waldeck et al 1996, Buchner and Barthel 2001, Heinz, van Gunsteren et al 2001, Kremer and Schönhals 2003, Rotenberg, Dufre Che et al 2005, Kuehn, Marohn et al 2006, Angulo-Sherman and Mercado-Uribe 2011. The practical importance of the time dependence is well known to the engineers who design solid state devices that work.…”
Section: Polarization Charge and Currentmentioning
confidence: 99%
“…In addition, by decomposing the dielectric constants into four component modes, a THz TD-ATR study found the fast relaxation mode was the collisional relaxation process originating from isolated water molecules, which implied ambient water should be regarded as two component mixtures [ 51 ]. Interestingly, another dielectric study also showed a magic point, isopermitive point, and gave an explanation on this point within the framework of two-component model [ 52 ]. However, the isosbestic point can also be interpreted from the viewpoint of tetrahedral arrangement of water molecules, or in other words continuum model [ 12 ], on condition that the variations in temperature and pressure are less than 100 K and 10 4 atm, respectively [ 11 ], which is the prerequisite for the insensitivity of equilibrium distribution of relevant coordinates to the surroundings.…”
Section: Water Structure Changes With Temperaturementioning
confidence: 99%
“…The increase in C sensor by the formation of water droplets on the IDE sensor surface ( Figure 6 ) is because the low dielectric medium of air (ε r,air = 1) in the air capacitor is partly replaced by the high dielectric water (with ε r,water = 50 at 10 kHz and 26 °C [ 26 ]). As reported in prior works, ε r,water decreased exponentially with the frequency in the measured range of 0.1–10 kHz [ 26 ], while ε r,PET decreased slightly with the frequency in 0.1–100 kHz [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%